Selective Janus kinase inhibition preserves interferon-λ-mediated antiviral responses - Schnepf, Daniel; Crotta, Stefania; Thamamongood, Thiprampai; Stanifer, Megan; Polcik, Laura; Ohnemus, Annette; Vier, Juliane; Jakob, Celia; Llorian, Miriam; Gad, Hans Henrik; Hartmann, Rune; Strobl, Birgit; et al. (Science immunology, 2021)
TYK2 is required for efficient IFN-α/β signaling but dispensable for IFN-λ-mediated antiviral protection in epithelial cells.